Neurological outcome in WDR62 primary microcephaly. (25th September 2021) - Ruaud, Lyse; Drunat, Séverine; Elmaleh‐Bergès, Monique; Ernault, Anais; Guilmin Crepon, Sophie; ,; El Ghouzzi, Vincent; Auvin, Stéphane; Verloes, Alain; Passemard, Sandrine
Abstract : Aim: To characterize the cortical structure, developmental, and cognitive profiles of patients with WD repeat domain 62 ( WDR62 ) ‐ related primary microcephaly. Method: In this observational study, we describe the developmental, neurological, cognitive, and brain imaging characteristics of 17 patients (six males, 11 females; mean age 12y 3mo standard deviation [SD] 5y 8mo, range 5y–24y 6mo) and identify 14 new variants of WDR62 . We similarly analyse the phenotypes and genotypes of the 59 previously reported families. Results: Brain malformations, including pachygyria, neuronal heterotopia, schizencephaly, and microlissencephaly, were present in 11 out of 15 patients. The mean full‐scale IQ of the 11 assessed patients was 51.8 (standard deviation [SD] 12.6, range 40–70). Intellectual disability was severe in four patients, moderate in four, and mild in three. Scores on the Vineland Adaptive Behavior Scales obtained from 10 patients were low for communication and motor skills (mean 38.29, SD 7.74, and 37.71, SD 5.74 respectively). The socialization score was higher (mean 47.14, SD 12.39). We found a significant difference between scores for communication and daily living skills (mean 54.43, SD 11.6; p =0.001, one‐way analysis of variance). One patient displayed progressive ataxia. Interpretation: WDR62 ‐related cognitive consequences may be less severe than expected because 3 out of 11 of the assessed patients had only mild intellectual disability and relatively preserved abilities of autonomy in daily life. We identified progressive ataxia in the second decade of life in one patient, which should encourage clinicians to follow up patients in the long term.